Comment on 'Analytical solution for transient, diffusing fields inside a ring conductor with rectangular cross section' [IET Sci. Meas. Technol., 2008, Vol. 2, No. 5, pp. 367–375]. Issue 5 (1st July 2020) - Gratkowski, Stanislaw; Ziolkowski, Marcin
Abstract : In the study, in the title of this comment, a ring conductor with rectangular cross‐section excited by ramped potentials at one end, with the other end grounded, has been considered. Analytical series solutions have been derived to describe the diffusing field transients in a few milliseconds in the ring conductor. This comment indicates the weaknesses of the study and presents an improved and much simpler analytical approach to the problem.